Gut Microbiota and Obesity in Adults and Children: The State of the Art - Maddalena Petraroli; Eleonora Castellone; Viviana Patianna; Susanna Esposito (Frontiers in Pediatrics, 2021)
In recent decades, obesity has become a serious public health problem affecting both children and adults. Considering the multifactorial origin of obesity, including modifiable factors, childhood was identified as the golden age for investing in obesity prevention by both promoting proper lifestyles and actively intervening in possible triggers. The gut microbiota is at the center of the most recent scientific studies and plays a key role in obesity development because it is intimately linked to energetic-humoral variations in the host: its alterations can promote a state of excessive energy storage, and it can be manipulated to maintain energy homoeostasis. This review aims to offer a panoramic understanding of the interplay between obesity and the gut microbiota, focusing on the contribution that the gut microbiota could have to the prevention of childhood obesity and its complications in adulthood. Currently, the use of some specific probiotic strains has been shown to be able to act on some secondary metabolic consequences of obesity (such as liver steatosis and insulin resistance) without any effect on weight loss. Although definitive conclusions cannot be drawn on the real impact of probiotics and prebiotics, there is no doubt that they represent an exciting new frontier in the treatment of obesity and associated metabolic dysfunctions. Targeted studies randomized on specific populations and homogeneous for ethnicity, sex, and age are urgently needed to reach definitive conclusions about the influence of microbiota on weight. In particular, we still need more studies in the pediatric population to better understand when the switch to an obese-like gut microbiota takes place and to better comprehend the right timing of each intervention, including the use of pre/probiotics, to improve it.